ANALYSIS OF GOLDFISH MARKETING IN PANGURURAN SUB-DISTRICT SAMOSIR REGENCY NORTH SUMATRA PROVINCE - Richard Halomoan Nainggolan; Hendrik Hendrik; Tince Sofyani (Fakultas Perikanan dan Kelautan, Universitas Riau, 2022)
Research on the marketing of Goldfish in Pangururan Sub-district Samosir Regency was carried out in April 2021. This research aimed to (1)analyzes the cost, Goldfish marketing advantage; (2) calculated marketing margin and efficiency of Goldfish marketing in Pangururan District North Sumatra Province. The method used in this research is the survey method by directed observation to the field. Respondents in this research were cultivators of as many as 22 people, collecting trades as many as 2 people, while the retailers is 10 people.The results of this research are known to collectors who buy Goldfish as much as 400 kg and sell to retailers as much as 40 kg per retailer. Average marketing cost incurred by the merchant by collecting trades amounting to IDR 453,33/kg and the average marketing costs incurred by retailers amounted to IDR 560/kg. For the marketing profit of collectors, the average amount is IDR 3.546,67/kg and for the profit of retailers, the average amount is IDR 1.440/kg. The marketing margin is IDR 6.000/kg and total fishermans share is 83,33%. Goldfish marketing in Pangururan District is efficient because Fishermans share bigger than 50%.